Addition to the Flora of Upper Gangetic Plain: Status of Solanum villosum Mill. a New Record from Bareilly, Uttar Pradesh - Kumar, Rajesh; Khare, A. K.; Singh, Hukum; Mishra, U. S. (Indian Forester, 2013)
No Abstract